How and Why We Should Argue with Angry Uncle: A Defense of Fact Dumping and Consistency Checking. (3rd September 2021) - Ferkany, Matt
ABSTRACT: How should we talk to Angry Uncle, or attempt to persuade any very ignorant audience? This paper discusses several strategies, including fact dumping, consistency checking, pandering, and just being friendly. It defends the continued value of fact dumping and consistency checking despite skeptical doubts rooted in recent cognitive science literature about their strategic efficacy. Pandering and friendliness often fail to confront our audience with epistemic resistance and so face serious limitations as means of responding to ignorance. Any reasonable view of how to talk to Angry Uncles must also consider how to meet relevant moral standards, such as showing respect for ourselves, our audience, and important social causes. Without some fact dumping and consistency checking, pandering and friendliness often fail to meet these standards. All in all, the various modes work best together, and it would be a mistake to conclude from unfavorable cognitive science research that we should avoid fact dumping and consistency checking in Angry Uncle exchanges.